Leibniz and Confucianism The Search for Accord - Mungello, D. E. (University of Hawai'i Press, 1977)
In the closing years of the seventeenth century, one of the most brilliant of modern European philosophers became actively involved in the search for intellectual and spiritual accord between Europe and China. In his search, Gottfried Wilhelm Leibniz entered the "Rites Controversy" on the side of the Jesuits, who had achieved positions of remarkable proximity to the Chinese throne. Yet less than forty years later, the optimism of their cause had dummed. Leibniz died in isolation in Hanover, the papacy ruled against the Jesuits at Rome, and in China there was a growing distrust of the Christian missionaries by the monarchy. In contrast to past neglect of this subject as an intriguing but peripheral area of Leibniz' philosophy, Leibniz and Confucianism: THe Search for Accord elevates Leibniz' interest in China to a more central concern of Leibnizian Ism. Leibniz was deeply committed to an ecumenism that included not only the reunion of Roman and Protestant Christendom, but an ecumenism with which the spiritual and intellectual beliefs and practices of non-Westerners, especially the Chinese, could be reconciled. As an investigation into how that commitment was pursued and into some of the reasons why it failed, this book seeks to present Leibniz' experience a both historical record and contemporary guide. Drawing upon unpublished material in the Leibniz archives in Hanover, Mungello traces the influences upon Leibniz through the Jesuit translators to the Chinese sources. In the process, we have the opportunity to observe the first historical instance of a major Western philosopher interpreting and reacting to Chinese (largely Neo-Confucian) philosophic notions and concepts. The author concludes by explaining how he believes Leibniz' search for accord can assist our own contemporary search for accord.